Members of Kemerovo Regional Counsil in the VKontakte Social Network: Engagement Metrics and Maria S. Gorodeshtyan’s Case - Filimonov Fedor; Mitin Aleksandr (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Council members (deputies) of the Kemerovo Regional Parliament are active in social networks, which they use as a platform for communication with citizens. The general sample covered entries and comments published by regional council members in the VKontakte social network between October 1, 2023, and January 28, 2024. The article also describes the relevant issues of SMM strategy revealed by a content analysis of publications made by council member Maria S. Gorodeshtyan, who ran for Governor of the Kemerovo Region in 2024. The analysis revealed a correlation between the publishing activity, the number of likes, and the indicators of ERpost, ERday, and TR. A combination of the correlation analysis based on engagement metrics with the qualitative content analysis made it possible to assess the effectiveness of political communication at the regional level. By adapting content strategies to specific initiatives and making emphasis on visualization, candidates can increase the trust of their potential voters. The case analysis yielded some recommendations for improving the content strategy: 1) more visual content (ERpost = 0.7); 2) shorter texts (≤160 characters) and more frequent posts (10 points); 3) focus on the small picture: detailed action plans and no vague language or abstract formulas; 4) more interaction: asking questions or suggesting topics to stimulate discussions in the comments; 5) optimal publication time during peaks of audience activity. The research contributes to the role of social networks as platforms of regional political campaigns and introduces a set of effective SMM methods.